Low-temperature rechargeable lithium ion battery and preparation method thereof
By using modified graphene and carbon-coated lithium titanate as negative electrode materials in lithium-ion batteries, the problems of low charging efficiency and safety hazards of lithium-ion batteries under low temperature conditions are solved, and higher cycle stability and specific capacity are achieved, broadening the application range.
Patent Information
- Application Number
- CN202510369644.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Under low temperature conditions, the charging efficiency of lithium-ion batteries is low and polarization is serious, resulting in insufficient power and may form lithium dendrites, causing safety hazards. Traditional electric vehicle power batteries are difficult to meet the needs of use.
Modified graphene and carbon-coated lithium titanate are used as the negative electrode material, and modified graphene is treated with fluorine doping to reduce defects on the negative electrode surface, reduce the risk of lithium ion aggregation and uneven deposition, and eliminate the formation of lithium dendrites.
It significantly improves the charging and discharging performance of lithium-ion batteries in low-temperature environments, enhances cycle stability and specific capacity, broadens the application range of lithium-ion batteries, and ensures the safety performance of electric vehicles.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a low-temperature charging lithium ion battery and a preparation method thereof. Background Art
[0002] Under low temperature conditions, the migration rate of lithium ions in the electrolyte and the diffusion rate in the negative electrode will decrease, resulting in aggravated polarization during charging, and the actual amount of electricity charged is far lower than the rated capacity of the battery. In addition, lithium ions that fail to be embedded in the graphite layers of the negative electrode in time will gather on the surface of the negative electrode and be reduced to metallic lithium, forming lithium dendrites. These lithium dendrites may pierce the battery separator, causing a short circuit and posing a safety hazard. Therefore, in a low temperature environment, traditional electric vehicle power batteries are difficult to meet the use requirements and cannot ensure the safety performance of electric vehicles.
[0003] At present, there are two commonly used solutions: one is to install a heating device in the battery module, but this heating system needs to quickly and evenly increase the module temperature in a short period of time so that the battery cell can work normally at a suitable temperature. It will not only consume part of the energy of the battery system, but the space occupied by the heating device will also reduce the energy density of the system, thereby adversely affecting the range of new energy vehicles; the second is to optimize the low-temperature performance of the single battery cell, and the main way is to select a suitable negative electrode material. However, there are currently few low-temperature resistant batteries available. The field urgently needs a low-temperature resistant battery that can be charged and discharged normally under low-temperature conditions of -40℃-0℃ without an external heating device. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a low-temperature rechargeable lithium-ion battery and a method for preparing the same. The lithium-ion battery prepared from the low-temperature rechargeable lithium-ion battery provided by the present invention can be used normally in a wide temperature environment, thereby broadening the application field of the lithium-ion battery.
[0005] To achieve the above object, the present invention adopts the following technical solutions: In one aspect, the present invention provides a low-temperature rechargeable lithium-ion battery, comprising modified graphene and carbon-coated lithium titanate; wherein the modified graphene is fluorine-doped carbon-coated graphene; Furthermore, the negative electrode material of the lithium-ion battery also includes a binder; Optionally, the binder includes one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polytetrafluoroethylene and polyimide; Further, the fluorine doping amount is 5wt%-15wt%; Specifically, the doping amount of fluorine can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%; Furthermore, in the negative electrode material of the lithium-ion battery, the mass ratio of the carbon-coated lithium titanate, the modified graphene and the binder is 8:1-3:0.5-1.5; Preferably, the mass ratio of the carbon-coated lithium titanate, the modified graphene and the binder is 8:1-3:0.8-1.2; More preferably, the mass ratio of the carbon-coated lithium titanate, the modified graphene and the binder is 8:2:1; Furthermore, the lithium-ion battery also includes an electrolyte, a positive electrode and a separator; Optionally, the electrolyte includes one or more of dimethyl carbonate, diethyl carbonate and ethylene carbonate; Optionally, the diaphragm includes one or more of a PP / PE diaphragm, a polyethylene terephthalate diaphragm, a poly(p-phenylene benzobisoxazole) diaphragm, a polyimide diaphragm, a modified glass fiber membrane, a coated diaphragm, and an electrospinning diaphragm; Optionally, the material of the positive electrode includes one or more of lithium sheet, lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium manganese oxide.
[0006] On the other hand, the present invention also provides a method for preparing a low-temperature charging lithium-ion battery, which comprises the following steps: (1) Preparation of modified graphene and carbon-coated lithium titanate; (2) Preparing negative electrode slurry: taking the modified graphene, then adding the carbon-coated lithium titanate, mixing evenly, adding a binder, mixing evenly again, adding deionized water, and stirring thoroughly to obtain a uniform negative electrode slurry; wherein the mass ratio of the carbon-coated lithium titanate, the modified graphene, the binder and the deionized water is 8:1-3:0.5-1.5:85-95; (3) Preparing a lithium-ion battery: The negative electrode slurry is evenly coated on a current collector, dried to obtain a pole piece, and then the pole piece is used as a negative electrode to prepare the lithium-ion battery.
[0007] Preferably, the mass ratio of the carbon-coated lithium titanate, the modified graphene, the binder and deionized water is 8:1-3:0.8-1.2:86-92; More preferably, the mass ratio of the carbon-coated lithium titanate, the modified graphene, the binder and deionized water is 8:2:1:88-90; Furthermore, the mass ratio of the carbon-coated lithium titanate, the modified graphene, the binder and the deionized water may also be 8:2:1:89; Furthermore, the specific steps of preparing the modified graphene in step (1) are: taking expanded graphite and dispersing it in an ethanol solution, then adding a carbon source 1, after uniform dispersion, freeze-drying to obtain a precursor 1, then heating the precursor 1 to 650-800°C at a heating rate of 4-6°C / min under an inert atmosphere and maintaining it for 5-7 h to obtain carbon-coated graphene, and then performing a fluorine doping treatment on the carbon-coated graphene to obtain modified graphene; Furthermore, the dispersion method in the step of dispersing the expanded graphite in the ethanol solution is ultrasonic dispersion, and the ultrasonic time is 2-4 hours, and the purpose of the ultrasound is to convert the expanded graphite into graphene; Further, the mass ratio of the expanded graphite to the carbon source 1 is 1-3:1; Specifically, the mass ratio of the expanded graphite to the carbon source 1 can be 1:1, 2:1, or 3:1; Further, the carbon source 1 includes one or more of ascorbic acid, citric acid, glucose and ethylene glycol citrate; Further, the specific step of fluorine doping the carbon-coated graphene includes: the specific step of fluorine doping the carbon-coated graphene includes: placing the carbon-coated graphene in a tubular reactor, replacing the reactor with N2, introducing a mixed gas of N2 and F2 in a molar ratio of 4-6:1, reacting a fluorine-nitrogen mixed gas at a temperature of 180-220°C for 6-8h, controlling the system pressure at 0.08-0.12Mpa, and the gas flow rate at 0.08-0.12 L / min, stopping the introduction of the fluorine-nitrogen mixed gas after fluorination for 1-3h, introducing nitrogen instead, and keeping warm for 1h to complete the preliminary fluorination reaction to obtain modified graphene. Preferably, the fluorine content in the modified graphene is 5wt%-15wt%; More preferably, the fluorine content in the modified graphene is 8wt%-12wt%; Furthermore, the specific steps of preparing carbon-coated lithium titanate in step (1) are as follows: taking Li2CO3 and TiO2, mixing and mixing, and after being fully dried, placing them in a muffle furnace and pre-calcining them at a temperature of 600-700°C for 10-14h, then adding them to anhydrous ethanol, mixing them evenly, filtering and drying them, placing the dried sample at a high temperature of 750-850°C and calcining them for 8-12h to obtain lithium titanate, and then ultrasonically dispersing the lithium titanate in deionized water, and then adding carbon source 2, mixing them evenly, and freeze-drying to obtain precursor 2, and then heating the precursor 2 to 650-800°C at a heating rate of 4-6°C / min in an inert atmosphere and maintaining it for 5-7h to obtain carbon-coated carbon-coated lithium titanate; Further, the molar ratio of the Li2CO3 to the TiO2 is 0.4-0.45:1; Specifically, the molar ratio of the Li2CO3 to the TiO2 may be 0.4:1, 0.41:1, 0.42:1, 0.425:1, 0.43:1, 0.44:1, 0.45:1; Furthermore, the mass ratio of the lithium titanate to the carbon source 2 is 5:2-4; Specifically, the mass ratio of the lithium titanate to the carbon source 2 can be 5:2, 5:3, or 5:4; Further, the carbon source 2 includes one or more of ascorbic acid, citric acid, glucose and ethylene glycol citrate; Furthermore, the specific steps of preparing the lithium-ion battery in step (3) are: uniformly coating the negative electrode slurry on the Cu current collector with a coating machine, vacuum drying, and obtaining the negative electrode; using a Li sheet as the positive electrode, selecting LiPFs as the solute, using an organic solution prepared from dimethyl carbonate, diethyl carbonate and ethylene carbonate in a volume ratio of 1:1:1 as the solvent as the electrolyte, and using a commercial PP / PE separator as the separator to obtain the lithium-ion battery.
[0008] In another aspect, the present invention further provides a low-temperature rechargeable lithium-ion battery, which is prepared by the above-mentioned preparation method.
[0009] Beneficial effects of the present invention: The present invention provides a low-temperature charging lithium-ion battery and a preparation method thereof, wherein the negative electrode material of the low-temperature charging lithium-ion battery includes modified graphene and carbon-coated lithium titanate, and the carbon-coated lithium titanate can reduce the defects on the negative electrode surface after being modified by modified graphene, reduce the risk of lithium ion aggregation and uneven deposition on the negative electrode surface, eliminate lithium dendrites generated by low-temperature charging, obtain a new negative electrode material with higher specific capacity, better cycle stability and lower lithium precipitation tendency, and significantly improve its low-temperature charging resistance. The low-temperature charging lithium-ion battery provided by the present application can also be used normally in a low-temperature environment, greatly broadening the application scope of lithium-ion batteries. DETAILED DESCRIPTION
[0010] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0011] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. In the description of the present application, it should be understood that "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In the present application, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple.
[0012] Example 1 This embodiment provides a low-temperature rechargeable lithium-ion battery and a preparation method thereof, and the specific steps are as follows: (1) Preparation of modified graphene: 10 g of expanded graphite was dispersed in an ethanol solution and ultrasonicated for 3 h, and then 5 g of glucose was added, and then ultrasonic stirring was continued for 0.5 h, and then freeze-dried to obtain a precursor 1, and then the precursor 1 was heated to 700 ° C at a heating rate of 5 ° C / min in a N2 atmosphere and maintained for 6 h to obtain carbon-coated graphene, and then the carbon-coated graphene was placed in a tubular reactor, and after the reactor was replaced with N2, a mixed gas of N2 and F2 in a molar ratio of 5:1 was introduced, and a fluorine-nitrogen mixed gas was reacted at a temperature of 200 ° C for 7 h, and the system pressure was controlled at 0.1 MPa, and the gas flow rate was controlled at 0.1 L / min. After fluorination for 2 h, the fluorine-nitrogen mixed gas was stopped, and nitrogen was introduced instead, and the temperature was kept for 1 h to complete the initial fluorination reaction to obtain modified graphene, wherein the fluorine content in the modified graphene is 10wt%; (2) Preparation of carbon-coated lithium titanate: With a stoichiometric ratio of n(Li / Ti)=0.85, 10 g of Li2CO3 and TiO2 powder were weighed, mixed and thoroughly dried, and then placed in a muffle furnace and pre-calcined at 650°C for 12 h. Subsequently, the mixture was added to 5 mL of anhydrous ethanol and ball-milled for 5 h. The mixture was then filtered and dried. The dried sample was calcined at 800°C for 10 h to obtain the product lithium titanate. 5 g of lithium titanate was then ultrasonically dispersed in deionized water. 3 g of glucose was then added. Ultrasonic stirring was continued for 0.5 h. Precursor 2 was freeze-dried to obtain precursor 2. Precursor 2 was then heated to 700°C at a heating rate of 5°C / min in a N2 atmosphere and maintained for 6 h to obtain carbon-coated lithium titanate. (3) Preparation of negative electrode material: Take the modified graphene and then add carbon-coated lithium titanate, ball mill for 4 hours, then add PAA (polyacrylic acid), continue ball milling for 1 hour, then add a small amount of deionized water as a solvent, stir thoroughly for 1 hour to obtain a uniform negative electrode slurry; wherein the mass ratio of carbon-coated lithium titanate, modified graphene, PAA and deionized water is 8:2:1:89; (4) Preparation of lithium-ion batteries: The negative electrode slurry was evenly coated on the Cu current collector with a coater, and then placed in a vacuum drying oven at 100°C for 12 hours to obtain the negative electrode; Li sheets were used as positive electrodes, LiPFs were selected as solutes, the solvent was an organic solution prepared from dimethyl carbonate, diethyl carbonate and ethylene carbonate in a volume ratio of 1:1:1 as the electrolyte, and the separator was a commercial PP / PE separator to prepare a lithium-ion battery.
[0013] Example 2 This embodiment provides a low-temperature rechargeable lithium-ion battery and a preparation method thereof, and the specific steps are as follows: (1) Preparation of modified graphene: 10 g of expanded graphite was dispersed in an ethanol solution and ultrasonicated for 3 h, and then 5 g of glucose was added, and then ultrasonic stirring was continued for 0.5 h, and then freeze-dried to obtain a precursor 1, and then the precursor 1 was heated to 700 ° C at a heating rate of 5 ° C / min in a N2 atmosphere and maintained for 6 h to obtain carbon-coated graphene, and then the carbon-coated graphene was placed in a tubular reactor, and after the reactor was replaced with N2, a mixed gas of N2 and F2 in a molar ratio of 5:1 was introduced, and a fluorine-nitrogen mixed gas was reacted at a temperature of 200 ° C for 7 h, and the system pressure was controlled at 0.1 MPa, and the gas flow rate was controlled at 0.1 L / min. After fluorination for 2 h, the fluorine-nitrogen mixed gas was stopped, and nitrogen was introduced instead, and the temperature was kept for 1 h to complete the initial fluorination reaction to obtain modified graphene, wherein the fluorine content in the modified graphene is 10wt%; (2) Preparation of carbon-coated lithium titanate: With a stoichiometric ratio of n(Li / Ti)=0.85, 10 g of Li2CO3 and TiO2 powder were weighed, mixed and thoroughly dried, and then placed in a muffle furnace and pre-calcined at 650°C for 12 h. Subsequently, the mixture was added to 5 mL of anhydrous ethanol and ball-milled for 5 h. The mixture was then filtered and dried. The dried sample was calcined at 800°C for 10 h to obtain the product lithium titanate. 5 g of lithium titanate was then ultrasonically dispersed in deionized water. 3 g of glucose was then added. Ultrasonic stirring was continued for 0.5 h. Precursor 2 was freeze-dried to obtain precursor 2. Precursor 2 was then heated to 700°C at a heating rate of 5°C / min in a N2 atmosphere and maintained for 6 h to obtain carbon-coated lithium titanate. (3) Preparation of negative electrode material: Take the modified graphene, then add carbon-coated lithium titanate, ball mill for 4 hours, then add PAA, continue ball milling for 1 hour, then add a small amount of deionized water as a solvent, stir thoroughly for 1 hour to obtain a uniform negative electrode slurry; wherein the mass ratio of carbon-coated lithium titanate, modified graphene, PAA and deionized water is 8:1:1:89; (4) Preparation of lithium-ion batteries: The negative electrode slurry was evenly coated on the Cu current collector with a coater, and then placed in a vacuum drying oven at 100°C for 12 hours to obtain the negative electrode; Li sheets were used as positive electrodes, LiPFs were selected as solutes, the solvent was an organic solution prepared from dimethyl carbonate, diethyl carbonate and ethylene carbonate in a volume ratio of 1:1:1 as the electrolyte, and the separator was a commercial PP / PE separator to prepare a lithium-ion battery.
[0014] Example 3 This embodiment provides a low-temperature rechargeable lithium-ion battery and a preparation method thereof, and the specific steps are as follows: (1) Preparation of modified graphene: 10 g of expanded graphite was dispersed in an ethanol solution and ultrasonicated for 3 h, and then 5 g of glucose was added, and then ultrasonic stirring was continued for 0.5 h, and then freeze-dried to obtain a precursor 1, and then the precursor 1 was heated to 700 ° C at a heating rate of 5 ° C / min in a N2 atmosphere and maintained for 6 h to obtain carbon-coated graphene, and then the carbon-coated graphene was placed in a tubular reactor, and after the reactor was replaced with N2, a mixed gas of N2 and F2 in a molar ratio of 5:1 was introduced, and a fluorine-nitrogen mixed gas was reacted at a temperature of 200 ° C for 7 h, and the system pressure was controlled at 0.1 MPa, and the gas flow rate was controlled at 0.1 L / min. After fluorination for 2 h, the fluorine-nitrogen mixed gas was stopped, and nitrogen was introduced instead, and the temperature was kept for 1 h to complete the initial fluorination reaction to obtain modified graphene, wherein the fluorine content in the modified graphene is 10wt%; (2) Preparation of carbon-coated lithium titanate: With a stoichiometric ratio of n(Li / Ti)=0.85, 10 g of Li2CO3 and TiO2 powder were weighed, mixed and thoroughly dried, and then placed in a muffle furnace and pre-calcined at 650°C for 12 h. Subsequently, the mixture was added to 5 mL of anhydrous ethanol and ball-milled for 5 h. The mixture was then filtered and dried. The dried sample was calcined at 800°C for 10 h to obtain the product lithium titanate. 5 g of lithium titanate was then ultrasonically dispersed in deionized water. 3 g of glucose was then added. Ultrasonic stirring was continued for 0.5 h. Precursor 2 was freeze-dried to obtain precursor 2. Precursor 2 was then heated to 700°C at a heating rate of 5°C / min in a N2 atmosphere and maintained for 6 h to obtain carbon-coated lithium titanate. (3) Preparation of negative electrode material: Take the modified graphene, then add carbon-coated lithium titanate, ball mill for 4 hours, then add PAA, continue ball milling for 1 hour, then add a small amount of deionized water as a solvent, stir thoroughly for 1 hour to obtain a uniform negative electrode slurry; wherein the mass ratio of carbon-coated lithium titanate, modified graphene, PAA and deionized water is 8:3:1:89; (4) Preparation of lithium-ion batteries: The negative electrode slurry was evenly coated on the Cu current collector with a coater, and then placed in a vacuum drying oven at 100°C for 12 hours to obtain the negative electrode; Li sheets were used as positive electrodes, LiPFs were selected as solutes, the solvent was an organic solution prepared from dimethyl carbonate, diethyl carbonate and ethylene carbonate in a volume ratio of 1:1:1 as the electrolyte, and the separator was a commercial PP / PE separator to prepare a lithium-ion battery.
[0015] Comparative Example 1 Compared with Example 1, the negative electrode slurry consists only of modified graphene, PAA and deionized water, and the composition ratio is 2:1:89, that is, the negative electrode material only includes modified graphene and PAA.
[0016] Comparative Example 2 Compared with Example 1, the negative electrode slurry consists only of carbon-coated lithium titanate, PAA and deionized water, and the composition ratio is 8:1:89, that is, the negative electrode material only includes carbon-coated lithium titanate and PAA.
[0017] Test analysis The lithium ion batteries prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to temperature resistance tests, and the electrical performance test method is as follows: Charging efficiency: 10 batteries were taken from each embodiment and comparative example, and the obtained batteries were first calibrated at 1C capacity at 25°C using a Xinwei capacity cabinet, and the discharge capacity C0 was recorded. Then, the batteries were allowed to stand for 24 hours at -20°C and -40°C, respectively, and charged at 1C constant current and constant voltage, and the charging capacity C1 of the batteries at -20°C and -40°C was recorded, respectively. Charging efficiency = C1 / C0×100%, and the average value of the calculated results was taken. The results are shown in Table 1.
[0018] Discharge efficiency: 10 batteries were taken from each embodiment and comparative example, and a Xinwei capacity cabinet was used. The obtained batteries were first calibrated at 1C capacity at 25°C, and the charging capacity C2 was recorded. Then, the batteries were allowed to stand at -20°C and -40°C for 24h, respectively, and discharged at 1C constant current and constant voltage, and the discharge capacity C3 was recorded. 1C discharge efficiency = C3 / C2×100%, and the average value of the calculated results was taken. The results are shown in Table 1.
[0019] Table 1 Charging efficiency (-20℃) Discharge efficiency (-20℃) Charging efficiency (-40℃) Discharge efficiency (-40℃) 1C discharge specific capacity / m·Ah / g 1C charge specific capacity / m·Ah / g Example 1 91.16% 96.28% 81.48% 87.74% 184.6 188.5 Example 2 90.03% 93.45% 80.90% 87.38% 182.2 185.7 Example 3 83.14% 88.69% 76.09% 81.62% 172.4 174.8 Comparative Example 1 48.56% 51.76% 30.65% 33.26% 145.6 148.4 Comparative Example 2 56.12% 63.83% 34.23% 42.48% 158.5 160.2 The lithium ion batteries prepared in Examples 1-3 and Comparative Examples 1-2 were charged at 1C in environments of -40°C, -20°C, and 0°C, respectively, and then the batteries were disassembled. The disassembled batteries were in a fully charged state. After disassembly, it can be observed that the negative electrode sheets of the lithium ion batteries prepared in Examples 1-3 were normal in the environments of -20°C and 0°C, without lithium precipitation, but there was slight lithium precipitation in the environment of -40°C. Although the lithium ion batteries prepared in Comparative Examples 1-2 had no obvious lithium precipitation when charged at 0°C, they had relatively obvious lithium precipitation in the environment of -20°C, especially in the environment of -40°C, both of them had very obvious lithium precipitation.
[0020] It can be seen from the above that the batteries prepared in Examples 1-3 of the present application have a charging efficiency of higher than 83.14% and a discharging efficiency of higher than 88.69% at a temperature of -20°C, and a charging efficiency of higher than 76.09% and a discharging efficiency of higher than 81.62% at a temperature of -40°C, which are much higher than those of Comparative Examples 1-2. It can be seen that the lithium-ion batteries prepared using the technical solution described in the present application have excellent electrochemical properties, especially low-temperature charging resistance.
[0021] The above is a detailed introduction to a low-temperature rechargeable lithium-ion battery and a preparation method thereof provided by the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A low temperature rechargeable lithium ion battery, characterized in that: The negative electrode material of the lithium-ion battery includes modified graphene and carbon-coated lithium titanate; Wherein, the modified graphene is fluorine-doped carbon-coated graphene.
2. The low temperature rechargeable lithium ion battery according to claim 1, characterized in that: The negative electrode material of the lithium ion battery also includes a binder.
3. The low temperature rechargeable lithium ion battery according to claim 2, characterized in that: In the negative electrode material of the lithium ion battery, the mass ratio of the carbon-coated lithium titanate, the modified graphene and the binder is 8:1-3:0.5-1.5; And / or, the binder includes one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polytetrafluoroethylene and polyimide.
4. The low temperature rechargeable lithium ion battery according to claim 1, characterized in that: The fluorine doping amount in the fluorine-doped carbon-coated graphene is 5wt%-15wt%; And / or, the lithium-ion battery also includes an electrolyte, a positive electrode and a separator; the electrolyte includes one or more of dimethyl carbonate, diethyl carbonate and ethylene carbonate; the separator includes one or more of PP / PE separator, polyethylene terephthalate separator, poly(p-phenylene benzobisazole) separator, polyimide separator, modified glass fiber membrane, coated separator, electrospinning separator; the material of the positive electrode includes one or more of lithium sheet, lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide and lithium manganese oxide.
5. A method for preparing a low-temperature rechargeable lithium-ion battery, characterized in that: The following steps are involved: (1) Preparation of modified graphene and carbon-coated lithium titanate; (2) Preparing negative electrode slurry: taking the modified graphene, then adding the carbon-coated lithium titanate, mixing evenly, adding a binder, mixing evenly again, adding deionized water, and stirring thoroughly to obtain a uniform negative electrode slurry; wherein the mass ratio of the carbon-coated lithium titanate, the modified graphene, the binder and the deionized water is 8:1-3:0.5-1.5:85-95; (3) Preparing a lithium-ion battery: The negative electrode slurry is uniformly coated on a current collector, dried to obtain a pole piece, and then the pole piece is used as a negative electrode to prepare the lithium-ion battery.
6. The method for preparing a low-temperature rechargeable lithium-ion battery according to claim 5, characterized in that: The specific steps of preparing the modified graphene in step (1) are: taking expanded graphite and dispersing it in an ethanol solution, then adding a carbon source 1, after uniform dispersion, freeze-drying to obtain a precursor 1, then heating the precursor 1 to 650-800°C at a heating rate of 4-6°C / min under an inert atmosphere and maintaining it for 5-7h to obtain carbon-coated graphene, and then performing a fluorine doping treatment on the carbon-coated graphene to obtain the modified graphene.
7. The method for preparing a low-temperature rechargeable lithium-ion battery according to claim 6, characterized in that: The dispersion method in the step of dispersing the expanded graphite in the ethanol solution is ultrasonic dispersion, and the ultrasonic time is 2-4h; And / or, the mass ratio of the expanded graphite to the carbon source 1 is 1-3:1; And / or, the carbon source 1 includes one or more of ascorbic acid, citric acid, glucose and ethylene glycol citrate; And / or, the specific steps of fluorine doping the carbon-coated graphene include: placing the carbon-coated graphene in a tubular reactor, replacing the reactor with N2, introducing a mixed gas of N2 and F2 in a molar ratio of 4-6:1, reacting a fluorine-nitrogen mixed gas at a temperature of 180-220°C for 6-8h, controlling the system pressure at 0.08-0.12Mpa, and the gas flow rate at 0.08-0.12 L / min. After fluorination for 1-3h, stopping the introduction of the fluorine-nitrogen mixed gas, introducing nitrogen instead, and keeping warm for 1h to complete the preliminary fluorination reaction to obtain modified graphene, wherein the fluorine content in the modified graphene is 5wt%-15wt%.
8. The method for preparing a low-temperature rechargeable lithium-ion battery according to claim 5, characterized in that: The specific steps of preparing carbon-coated lithium titanate in step (1) are as follows: take Li2CO3 and TiO2, mix them evenly, dry them thoroughly, place them in a muffle furnace and pre-calcine them at 600-700°C for 10-14h, then add them to anhydrous ethanol, mix them evenly, filter and dry them, place the dried sample at a high temperature of 750-850°C and calcine it for 8-12h to obtain lithium titanate, then ultrasonically disperse the lithium titanate in deionized water, then add carbon source 2, mix them evenly and freeze-dry them to obtain precursor 2, then heat the precursor 2 to 650-800°C at a heating rate of 4-6°C / min in an inert atmosphere and keep it for 5-7h to obtain carbon-coated carbon-coated lithium titanate.
9. The method for preparing a low-temperature rechargeable lithium-ion battery according to claim 8, characterized in that: The molar ratio of Li2CO3 to TiO2 is 0.4-0.45:1; And / or, the mass ratio of the lithium titanate to the carbon source 2 is 5:2-4; And / or, the carbon source 2 includes one or more of ascorbic acid, citric acid, glucose and ethylene glycol citrate.
10. The method for preparing a low-temperature rechargeable lithium-ion battery according to claim 5, characterized in that: The specific steps of preparing the lithium-ion battery in step (3) are: uniformly coating the negative electrode slurry on the Cu current collector with a coating machine, and vacuum drying to obtain the negative electrode; using a Li sheet as the positive electrode, selecting LiPFs as the solute, using an organic solution prepared from dimethyl carbonate, diethyl carbonate and ethylene carbonate in a volume ratio of 1:1:1 as the solvent as the electrolyte, and using a commercial PP / PE separator as the separator to prepare the lithium-ion battery.
Citation Information
Patent Citations
Lithium titanate composite material, preparation method thereof, and application thereof
CN102468485A
Preparation method of lithium titanate-graphene composite material
CN103490040A
Preparation method of carbon-modified nano Li4Ti5O12-porous graphene composite electrode material
CN103500822A
Preparation method of fluorine and nitrogen codoped graphitized carbon microspheres with high volume specific capacitance
CN104103430A
Lithium titanate composite negative electrode material and preparation method thereof
CN114551844A